2000
DOI: 10.1034/j.1600-079x.2001.280304.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol and lipid peroxidation are decreased by melatonin in diet‐induced hypercholesterolemic rats

Abstract: The purpose of this study was to investigate the effect of melatonin, at pharmacological doses, on serum lipids of rats fed with a hypercholesterolemic diet. Therefore, different groups of animals were fed with either the regular Sanders Chow diet or a diet enriched in cholesterol. Moreover, animals were treated with or without melatonin in the drinking water for 3 months. We show that melatonin treatment did not affect the levels of cholesterol or triglycerides in rats fed with a regular diet. However, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
82
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 27 publications
7
82
2
2
Order By: Relevance
“…Changes observed in this study in the cholesterol levels of melatonin-treated cows are at variance with the data published previously. In studies on rats fed a diet high in cholesterol, melatonin lowered the level of this metabolite, while it did not cause any changes in rats fed a normal diet (Mori et al, 1989;Hoys et al, 2000). However, in the present experiment the pineal gland hormone caused an increase in the level of this variable, which seems advantageous from the aspect of interest of our study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Changes observed in this study in the cholesterol levels of melatonin-treated cows are at variance with the data published previously. In studies on rats fed a diet high in cholesterol, melatonin lowered the level of this metabolite, while it did not cause any changes in rats fed a normal diet (Mori et al, 1989;Hoys et al, 2000). However, in the present experiment the pineal gland hormone caused an increase in the level of this variable, which seems advantageous from the aspect of interest of our study.…”
Section: Discussioncontrasting
confidence: 50%
“…For this reason melatonin may affect -directly or indirectly -the metabolism of a given organism (Vanecek, 1998;Maćkowiak et al, 1999a, b). The advantageous effects of melatonin on carbohydrate-lipid metabolism (Maćkowiak et al, 1999a, b;Hoys et al, 2000) as well as on the endocrine status (Maćkowiak et al, 1999a;Esquifino et al, 1999;Fabiś et al, 2002) have already been demonstrated.…”
mentioning
confidence: 99%
“…Lipid peroxidation is a basically degenerative reaction and its products such as TBARS are toxic to cells (24)(25)(26). As mentioned above, melatonin has been shown to be highly effective in protecting against oxidative damage caused by several factors such as aging, ischemia-reperfusion, toxins and hypercholesterolemia (17,(27)(28)(29)(30). The present data also indicate the oxidant activity of ethanol on lipids.…”
Section: Discussionsupporting
confidence: 56%
“…Melatonin is a highly potent endogenous radical scavenger protecting the biomolecules against oxidative modifi cation (15). Melatonin administration has been shown to have no signifi cant effect on plasma lipids and lipoproteins in rats on normal diet but diminishes the effects of high-cholesterol diet on lipid parameters (14,17). The protective action of melatonin was manifested only following the induction of cholesterolemia in rats (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation